The effect of isocapnic hyperoxia on neurophysiology as measured with MRI and MEG - Croal, Paula L.; Hall, Emma L.; Driver, Ian D.; Brookes, Matthew Jon; Gowland, Penny A.; Francis, Susan T. (Elsevier, 2015)
The physiological effect of hyperoxia has been poorly characterised, with studies reporting conflicting results on the role of hyperoxia as a vasoconstrictor. It is not clear whether hyperoxia is the primary contributor to vasoconstriction or whether induced changes in CO2 that commonly accompany hyperoxia are a factor. As calibrated BOLD fMRI based on hyperoxia becomes more widely used, it is essential to understand the effects of oxygen on resting cerebral physiology. This study used a RespirActTM system to deliver a repeatable isocapnic hyperoxia stimulus to investigate the independent effect of O2 on cerebral physiology, removing any potential confounds related to altered CO2. T1-independent Phase Contrast MRI was used to demonstrate that isocapnic hyperoxia has no significant effect on carotid blood flow (normoxia 201 ± 11 ml/min, -0.3 ± 0.8 % change during hyperoxia, p = 0.8), whilst Look Locker ASL was used to demonstrate that there is no significant change in arterial cerebral blood volume (normoxia 1.3 ± 0.4 %, -0.5 ± 5 % change during hyperoxia). These are in contrast to significant changes in blood flow observed for hypercapnia (6.8 ± 1.5 %/mmHg CO2). In addition, magnetoencephalography provided a method to monitor the effect of isocapnic hyperoxia on neuronal oscillatory power. In response to hyperoxia, a significant focal decrease in oscillatory power was observed across the alpha, beta and low gamma bands in the occipital lobe, compared to a more global significant decrease on hypercapnia. This work suggests that isocapnic hyperoxia provides a more reliable stimulus than hypercapnia for calibrated BOLD, and that previous reports of vasoconstriction during hyperoxia probably reflect the effects of hyperoxia-induced changes in CO2. However, hyperoxia does induce changes in oscillatory power consistent with an increase in vigilance, but these changes are smaller than those observed under hypercapnia. The effect of this change in neural activity on calibrated BOLD using hyperoxia or combined hyperoxia and hypercapnia needs further investigation.